Tingkat Pematangan Inti Oosit Domba dan Pembentukan Pronukleus Setelah Parthenogenesis dengan Penambahan Glutathione (NUCLEAR MATURATION RATE OF OVINE OOCYTES AND PRONUCLEAR FORMATION AFTER PARTHENOGENESIS WITH GLUTATHIONE ADDITION) - ., Hasbi; Gustina, Sri; Setiadi, Mohamad Agus; Supriatna, Iman (Jurnal Veteriner; Vol 13 No 4 (2012), 2013)
The aim of this study was to investigate the nuclear maturation rate of ovine oocytes and pronuclearformation following parthenogenesis with glutathione (GSH) addition in maturation and culture medium.In the first experiment, acolytes were matured in tissue culture medium (TCM) 199 with 0 (control), 0.25,0.5 and 1 mM glutathione (GSH) addition. In the second experiment, oocytes were matured in maturationmedium, then parthenogenetically activated by exposing to 7% ethanol (v/v) for 7 min, followed by treatmentwith 5 ìg/ml cytochalasin B for 4 h. Oocytes then cultured in medium TCM 199 + 10% FBS with treatmentswithout addition of 1 mM GSH (T0), addition in maturation medium (T1), addition in culture medium (T2),and addition in both maturation and culture medium (T3) then incubated at 38,5oC with 5% CO2 for 20-24h. The results showed that, nuclear maturation rate was not significantly different (P>0.05) among fourtreatments. The percentage of oocytes reached metaphases II (MII) stage were 79.71%, 79.07%, 80.95%and 84.13%, respectively. Percentages of activated oocyte with T1 (65.31%) and T3 (67.27%) were higher(P<0.01) compared to T0 (46.81%) and T2 (54.35%). However, T3 was not significantly different with T1. Inconclusion, the addition of GSH in maturation medium could not improve nuclear maturation rate butmore effective in supporting the number of activated oocytes.
Keywords: glutathione, maturation, parthenogenesis, ovine oocytes